KONSEP ONTOLOGI DAKWAH SUNAN KALIJOGO RELEVANSINYA BAGI PERKEMBANGAN MASYARAKAT PADA MASA KINI - wahyudin wahyudin wahyudin (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
The figures spread the religion of Islam in Java will not be separated from the role of Walisongo in the grounding of Islamic teachings are very famous and especially sunan Kalijogo. The fame of Kalijogo sunan because he is a magic scholar and intelligent. He is a politician who raises the kings of some Islamic kingdoms, and is known as a well-mannered humanist and well-known puppet artist and artist. The historical review of Javanese society at that time still feels so reluctant to throw away the old teachings that are firmly attached. So depart from the thought in order to achieve its goals and ease in the spread of Islam in the land of Java, without the intention to mix up shari'ah with ancestral culture, sunan kalijogo make existing treasures as a means to neutralize the ancient society's assumptions Still leads to idolatry. This ontological concept will reveal a new horizon about the impression on the story of walisongo, especially Kalijogo that tend to be less valuable among the masyarkat, especially Muslims. If an ontological horizon or nuance is found and a new image of walisonggo Sunan Kalijogo will tend to be uniform and thus will bring the distance between a story that is known to a more rational one. In turn, a new picture of Indonesian history in which local wisdom can be explained more clearly can be explained through the nuances of ontology as part of the philosophical study.